2001
DOI: 10.1590/s0102-76382001000400001
|View full text |Cite
|
Sign up to set email alerts
|

O uso da artéria torácica interna no idoso: indicações e resultados imediatos

Abstract: INTRODUÇÃODados demográficos recentes demonstram que a população de idosos no Brasil, seguindo a tendên-cia dos países desenvolvidos, vem apresentando constante crescimento (www.datasus.gov.br). Com melhores acessos aos sistemas de saúde e a grande prevalência de doenças ateroscleróticas dos países ocidentais, atenção especial deve ser dada a esta parcela da população que necessita de tratamento para insuficiência coronária. Hoje, esses RESUMO: Objetivo: A artéria torácica interna é o enxerto de eleição para r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
6
1
1
Order By: Relevance
“…The analysis of our case material showed that 61 patients (37%) had three or more revascularized arteries, and that in 97% of cases the left anterior descending artery was involved. However, unlike other reports 15,16 , in which the left internal mammary artery was used in over 95% of cases, in our series this type of graft was used in 57% of patients. The low percentage is due to the fact that up to 2000, we did not routinely use the LITA in patients over 75 years, and we still do not use it in emergency surgeries with hemodynamic instability.…”
Section: Discussioncontrasting
confidence: 69%
“…The analysis of our case material showed that 61 patients (37%) had three or more revascularized arteries, and that in 97% of cases the left anterior descending artery was involved. However, unlike other reports 15,16 , in which the left internal mammary artery was used in over 95% of cases, in our series this type of graft was used in 57% of patients. The low percentage is due to the fact that up to 2000, we did not routinely use the LITA in patients over 75 years, and we still do not use it in emergency surgeries with hemodynamic instability.…”
Section: Discussioncontrasting
confidence: 69%
“…O uso rotineiro da ATIE como enxerto de primeira escolha em pacientes idosos mostrou ser seguro e eficaz (26) . A ATIE, como única fonte de suprimento sangüíneo para mais de uma coronária, de forma seqüencial, em "Y" ou em "T", utilizando enxerto de safena ou de artéria radial, é descrito na literatura, sobretudo para revascularizar pacientes com alto risco para AVC, com bons resultados (7,(27)(28)(29) .…”
Section: Resultsunclassified
“…Tyszka & Fucuda [16] observed that the use of internal thoracic artery brings no increase in morbidity and even improves the early and late survival and should therefore be considered as a graft of first choice for the elderly.…”
Section: Discussionmentioning
confidence: 99%